Identification of QTLs with effects on seed coat appearance in cowpea - Sodo, A.M.I.; Fatokun, C.; Olasanmi, B.; Ongom, P.O.; Dieng, I.; Boukar, O. (2025)
Cowpea (Vigna unguiculata [L.] Walp.) is a key protein source in sub-Saharan Africa, and seed coat appearance traits such as pigmentation and texture are critical for market segments (MS). We investigated the genetic basis of these traits using 316 recombinant inbred lines derived from a cross between the landrace RP270 (white coat – colorless eye) and the improved variety CB27 (white coat – black seed eye) over two years under regular rainfed conditions. A panel of 2602 high-quality DArTag single nucleotide polymorphisms (SNPs) was used to genotype the RIL population. A total of 30 main QTLs associated with seed coat appearance were identified with phenotypic variation explained ranging from 1.2% to 78.4%. Epistatic analysis revealed 116 significant digenic interactions, highlighting the complex inheritance of pigmentation traits. Based on gene ontology and available literature, we highlighted 12 candidate genes involved in the regulation of seed coat pigmentation in cowpea grains. These findings provide a basis for further research on the genetics of cowpea pigmentation and support future work on map-based cloning of candidate genes and marker-assisted cowpea breeding programs.